Developing English for Tourism Materials Course based on Banten Local Wisdom - Sutrisno Sadji Evenddy; Ledy Nurlely; Suroso Mukti Leksono (Universitas Cokroaminoto Palopo, 2022)
By examining Banten's local wisdom, this paper intends to investigate the evolution of English for Tourism teaching materials. This article examines the concept of material development, material development principles, material development requirements analysis, and local wisdom as a point in the construction of teaching materials. The following section covers the material development process and analyzes the development of English Tourism course materials based on local knowledge. This article also offers advice on how to incorporate local knowledge into material development and how to create useful materials for an English for Tourism course.